{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

sol-310c

# sol-310c - 310c Homework Solutions 2010 Homework 1 Solution...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 310c: Homework Solutions 2010 Homework 1 Solution. 7.1.12 Fixing h > 0 and t ≥ 0, let Y = X t + h- X t and L = { A ∈ F : P ( A ∩ C ) = P ( A ) P ( C ) for all C ∈ σ ( Y ) } . Note that L is a λ-system. Also, for s = ( s 1 , . . . , s m ) such that 0 ≤ s 1 < ··· < s m = t considering our assumption that X s 1 , X s 2- X s 1 , ··· , X s n- X s n- 1 are P-mutually independent, with and without s m +1 = t + h , we deduce from Definition 1.4.3 that { X s 1 ∈ B 1 } T m k =2 { X s i- X s k- 1 ∈ B k } ∈ L for any ( B 1 , B 2 , ··· , B m ) ∈ B m . Since this π-system generates F s = σ ( X s 1 , X s 2- X s 1 , ··· , X s m- 1- X s m ), by Dynkin’s π- λ theorem we have that F s ⊆ L . The measurable map from ( X s 1 , X s 2 , ··· , X s m ) to ( X s 1 , X s 2- X s 1 , ··· , X s m- X s m- 1 ) is invertible, hence F s = σ ( X s 1 , X s 2 , ··· , X s m ) (see Exercise 1.2.30). Let P = ∪ s F s where the union is over all finite sets s ⊆ [0 , t ]. Since P is a π-system, appealing once more to the π- λ theorem you conclude that F X t = σ ( P ) ⊆ L . That is, as claimed X t + h- X t is independent of F X t . Solution. 7.1.13 Given A 1 , . . . , A n ∈ T , we define the corresponding f.d.d. as follows. First set B k 1 = A k = B c k for k = 1 , . . . , n and note that by monotonicity of A 7→ μ ( A ), for each non-zero b = ( b 1 , . . . , b n ) ∈ { , 1 } n the set A b = T k B kb k is in T . With N b a Poisson( μ ( A b )) random variable independent of { N b , b 6 = b } , let the random vector ( N A 1 , . . . , N A n ) have the same law as ( ∑ { b : b k =1 } N b , k = 1 , . . . , n ). Then, considering n = 1 we see that N A has the Poisson( μ ( A )) law for each A ∈ T . Moreover, if A k , k = 1 , . . . , n are disjoint sets then ∑ k b k > 1 yields A b = ∅ and hence N b ≡ 0. So, in this case our construction results with mutually independent N A k , k = 1 , . . . , n . Turning to check that these f.d.d. are consistent, fix n and a permutation π : { 1 , . . . , n } → { 1 , . . . , n } . Note that for index sets { A π ( k ) } the preceding constructs mutually independent N ( b π (1) ,...,b π ( n ) ) of Poisson( μ ( A b )) laws, hence the resulting law of ( N A π (1) , . . . , N A π ( n ) ) is merely the image of the law of ( N A 1 , . . . , N A n ) under the permutation π of the coordinates. That is, the identity (7.1.1) holds (where A k ∈ T serve as the index points t k there). Next, fixing { A k , k ≤ n } and non- zero b ∈ { , 1 } n- 1 , since A b is the disjoint union of A b , and A b , 1 we have by finite additivity of μ ( · ) that μ ( A b ) = μ ( A b , ) + μ ( A b , 1 ). This applies for any non- zero b , so by the thinning property of Poisson variables we have the representation N b = N b , + N b , 1 (see Exercise 3.4.16, part (a)), and as a result the identity (7.1.2) also holds....
View Full Document

{[ snackBarMessage ]}

### Page1 / 12

sol-310c - 310c Homework Solutions 2010 Homework 1 Solution...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online